Lawful kinematics link eye movements to the limits of high-speed perception - Martin Rolfs; Richard Schweitzer; Eric Castet; Tamara L. Watson; Sven Ohl (Nature Communications)
Abstract Perception requires active sampling of the environment. What part of the physical world can be perceived is limited by the sensory system’s biophysical setup, but might be further constrained by the kinematic bounds of the motor actions used to acquire sensory information. Here, we tested this fundamental idea for humans’ fastest and most frequent behavior—saccadic eye movements—which entail incidental sensory consequences (i.e., swift retinal motion) that rarely reach awareness in natural vision. Using high-speed video projection, we display rapidly moving stimuli that faithfully reproduce, or deviate from, saccades’ lawful relation of velocity, duration, and amplitude. For each stimulus, observers perform perceptual tasks for which performance is contingent on consciously seeing the stimulus’ motion trajectory. We uncover that visibility of the stimulus’ movement is well predicted by the specific kinematics of saccades and their sensorimotor contingencies, reflecting even variability between individual observers. Computational modeling shows that spatiotemporal integration during early visual processing predicts this lawful relation in a tight range of biologically plausible parameters. These results suggest that the visual system takes into account motor kinematics when omitting an action’s incidental sensory consequences, thereby preserving visual sensitivity to high-speed object motion.